The African Philosophy of Ubuntu in South African Education - Baken Johannes Lefa (LPPM - Sekolah Tinggi Teologi Indonesia Jakarta, 2026)
Ubuntu lies at the heart of the African way of life and impacts on every aspect of people’s well-being. This paper seeks to explore the notion of being human by grounding discussions around the concept of what is generally referred to as Ubuntu in South African education and society. The issue of discipline in schools or in education is selected as a way to demonstrate the concept of Ubuntu mostly amongst learners and teachers or either the school environment. Ubuntu is actually regarded as the soul force that drives almost every facet of societal life in African societies and that create the relationship between the African community. In this paper I will be mostly focusing on Ubuntu in education or rather in South African schools. This paper seeks to understand how Ubuntu impacts on discipline in South African schools. Ubuntu in the South African context or society is seen as the act of being human, caring, sympathy, empathy, forgiveness or any values of humanness towards others. Ubuntu is a capacity in South African culture that expresses compassion, reciprocity, dignity, harmony and humanity in the interests of building and maintaining a community with justice and mutual caring. The consequences of failure to embrace Ubuntu in South African Schools manifest itself through learner’s indiscipline and staff not respecting each other. The purpose of this paper is to place the reader in South African society and introduce the concept of Ubuntu as the Philosophy of the society in relation to education.